On the Uniqueness and Dependence of Positive Periodic Solutions for Delay Differential Systems with Feedback Control - Haitao Li; Yansheng Liu (International Journal of Mathematics and Mathematical Sciences)
This paper investigates a class of delay differential systems with feedback control. Sufficient conditions are obtained for the existence and uniqueness of the positive periodic solution by utilizing some results from the mixed monotone operator theory. Meanwhile, the dependence of the positive periodic solution on the parameter λ is also studied. Finally, an example together with numerical simulations is worked out to illustrate the main results.